Streptomyces lonarensis sp nov., isolated from lonar lake, a meteorite salt water lake in India - Sharma, Trupti K.; Mawlankar, Rahul R.; Sonalkar, Vidya V.; Shinde, Vidhya K.; Zhan, Jing; Li, Wen-Jun; Rele, Meenakshi V.; Dastager, Syed Gulam; Kumar, Lalitha Sunil (Antonie Van Leeuwenhoek International Journal of General and Molecular Microbiology, 2016)
A novel alkaliphilic actinomycete, strain NCL716(T), was isolated from a soil sample collected from the vicinity of Lonar Lake, an alkaline salt water meteorite lake in Buldhana district of Maharashtra State in India. The strain was characterised using a polyphasic taxonomic approach which confirmed that it belongs to the genus Streptomyces. Growth was observed over a pH range of 7-11 at 28 A degrees C. The cell wall was found to contain ll-diaminopimelic acid and traces of meso-diaminopimelic acid. The major fatty acid components were identified as iso-C-16:0 (46.8 %), C-17:1 (12.4 %), anteiso-C-15:0 (5.1 %) and anteiso-C-17:1 (4.8 %). The major polar lipids were identified as diphosphatidylglycerol, phosphatidylethanolamine, phosphatidylglycerol and phosphatidylinositol. The major menaquinones were determined to be MK-9 (H-6) (70.3 %), MK-9 (H-4) (15.5 %) and MK-9 (H-8) (7.2 %). The G+C content of the DNA of the type strain was determined to be 71.4 mol %. The 16S rRNA gene sequence has been deposited in GenBank with accession number FJ919811. Although the 16S rRNA gene sequence analysis revealed that strain NCL716(T) shares > 99 % similarity with that of Streptomyces bohaiensis strain 11A07(T), DNA-DNA hybridization revealed only 33.2 +/- A 3.0 % relatedness between them. Moreover, these two strains can be readily distinguished by some distinct phenotypic characteristics. Hence, on the basis of phenotypic and genetic analyses, it is proposed that strain NCL716(T) represents a novel species of the genus Streptomyces, for which the name Streptomyces lonarensis sp. nov., is proposed. The type strain is NCL 716(T) (=DSM 42084(T) = MTCC 11708(T) = KCTC 39684(T)).
Keywords: Alkaliphile; DDH analysis; Polyphasic taxonomy; Streptomyces lonarensis sp nov.

Secondary structure of the internal transcribed rDNA (ITS) regions of cosmopolites sordidus (Germar) and odoiporus longicollis (Olivier): a first report in family Curculionidae - Kumar, Lalitha Sunil (International Journal of Tropical Insect Science, 2019)
In the present work the consensus secondary structure of the internal transcribed rDNA spacers ITS1 and ITS2 of two weevils i.e. Cosmopolites sordidus (Germar) and Odoiporus longicollis (Olivier) has been described. The secondary structures of the ITS1 region of C.sordidus and O.longicollis have ten and five helices respectively, emerging from a central core. Two and five helices emerge from a central core in the ITS2 secondary structures of C.sordidus and O.longicollis respectively, and do not conform to the `paneukaryotic' four domain model. The ITS2 sequences of these two weevils share three regions with maximum sequence identity. Of these, two are present at the 5' and 3' end and share structural similarity, suggesting their possible role in the processing of the rRNA. This is the first report of the secondary structure of the ITS region in family Curculionidae which can serve as a valuable resource for homology modelling and phylogenetic studies.
Keywords: Cosmopolites sordidus (Germar); Curculionidae; ITS1; ITS2; Odoiporus longicollis (Olivier); Secondary structure